2023
DOI: 10.3389/fphar.2023.1102810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymorphisms in drug metabolism and transportation on plasma concentration of atorvastatin and its metabolites in patients with chronic kidney disease

Abstract: Dyslipidemia due to renal insufficiency is a common complication in patients with chronic kidney diseases (CKD), and a major risk factor for the development of cardiovascular events. Atorvastatin (AT) is mainly used in the treatment of dyslipidemia in patients with CKD. However, response to the atorvastatin varies inter-individually in clinical applications. We examined the association between polymorphisms in genes involved in drug metabolism and transport, and plasma concentrations of atorvastatin and its me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Candidate single nucleotide polymorphisms (SNPs) were mainly selected from previously reported literature, which may potentially affect tacrolimus pharmacokinetics in solid‐organ transplantation. All SNPs and their respective genes analyzed in this study are listed in Table S1 5,8,16–30 . For genotyping, briefly, a 0.5‐mL blood sample was collected and genomic DNA was extracted from ethylenediaminetetraacetic acid‐anticoagulated peripheral blood samples using a commercially available DNA purification kit (EasyPure Blood Genomic DNA Kit, Transgene Biotech).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate single nucleotide polymorphisms (SNPs) were mainly selected from previously reported literature, which may potentially affect tacrolimus pharmacokinetics in solid‐organ transplantation. All SNPs and their respective genes analyzed in this study are listed in Table S1 5,8,16–30 . For genotyping, briefly, a 0.5‐mL blood sample was collected and genomic DNA was extracted from ethylenediaminetetraacetic acid‐anticoagulated peripheral blood samples using a commercially available DNA purification kit (EasyPure Blood Genomic DNA Kit, Transgene Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…All SNPs and their respective genes analyzed in this study are listed in Table S1. 5,8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] For genotyping, briefly, a 0.5-mL blood sample was collected and genomic DNA was extracted from ethylenediaminetetraacetic acid-anticoagulated peripheral blood samples using a commercially available DNA purification kit (EasyPure Blood Genomic DNA Kit, Transgene Biotech). All samples with a call rate greater than 95% were genotyped using an Infinium Asian Screening Array-China Health Industry Alliance Bead chip (Illumina, Inc.) according to the Illumina Infinium HTS chip standard operating procedures.…”
Section: Genotypingmentioning
confidence: 99%
“…Data from in vitro studies have reported that CYP3A4 and CYP3A5 were responsible for 85% and 15% of atorvastatin metabolism, respectively [8,14]. AC is first transformed into its lactone form and subsequently into two pharmacologically active metabolites (2-hydroxyatorvastatin and 4-hydroxy-atorvastatin) by these enzymes [3,15]. Aside from metabolic enzymes, AC also heavily rely on drug transporter proteins for its disposition and efficacy [3,6].…”
Section: Introductionmentioning
confidence: 99%